2007
DOI: 10.1364/oe.15.008135
|View full text |Cite
|
Sign up to set email alerts
|

Detection of small particles in fluid flow using a self-mixing laser

Abstract: We describe a highly sensitive, real-time method of detecting small particles in a fluid flow by self-mixing laser Doppler measurement with a laser-diode-pumped, thin-slice solid-state laser with extremely high optical sensitivity. Asymmetric power spectra of the laser output modulated by the re-injected scattered light from the small particles moving in a dilute sample-flow, through a small-diameter glass pipe, were observed. The observed power spectra are shown to reflect the velocity distribution of the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…In this case, the power spectrum of the modulated wave induced by the Brownian motion of the particles becomes Lorentzian. On the other hand, we also demonstrated that self-mixing LDV is applicable to velocimetry of the fluid flow containing nanosize tracer particles through a glass pipe [6,7]. In this case, the power spectrum has a complex line shape because the velocity distribution of the particles in the pipe obeys Poiseuille's law.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In this case, the power spectrum of the modulated wave induced by the Brownian motion of the particles becomes Lorentzian. On the other hand, we also demonstrated that self-mixing LDV is applicable to velocimetry of the fluid flow containing nanosize tracer particles through a glass pipe [6,7]. In this case, the power spectrum has a complex line shape because the velocity distribution of the particles in the pipe obeys Poiseuille's law.…”
Section: Introductionmentioning
confidence: 78%
“…Thus, the velocity of the target can be obtained from the observation of the intensity-modulated laser light. We have developed several self-mixing LDV systems with thin-slice solid-state lasers, such as a selfmixing particle analyzer [5,6] and a flowmeter [6,7]. Solid-state lasers with highly doped active ions having an extremely short absorption length for laser-diode pumping are suitable for thin-slice cavity configurations, and these lasers result in an extremely short photon lifetime compared with fluorescence lifetimes.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the fitting procedure is as follows: Thirty Gaussian functions are set within the observed power spectrum, whose center frequencies f Di are equally spaced, to describe the velocity distributions. v i -values are derived using Equation (14) and w i -values are determined using the empirical relation, w i = 574,100 v i , which was experimentally obtained from the Gaussian curve fitting of time dependent power spectra for 262-nm-diameter PS particles in ‘dropped water’ from the vertical pipe shown in Figure 15 [40]. Here, the velocity distribution of the PS particles in the light path is very small, i.e.…”
Section: Multiple-channel Self-mixing Laser Doppler Measurement With mentioning
confidence: 99%
“…v i -values are derived using Equation (14) and w i -values are determined using the empirical relation, w i = 574,100 v i , which was experimentally obtained from the Gaussian curve fitting of time dependent power spectra for 262-nm-diameter PS particles in ‘dropped water’ from the vertical pipe shown in Figure 15 [40]. Here, the velocity distribution of the PS particles in the light path is very small, i.e.…”
Section: Multiple-channel Self-mixing Laser Doppler Measurement With mentioning
confidence: 99%
See 1 more Smart Citation